EXPLORING SPEECH ACTS IN THE SHORT FILM "VALIDATION" - Nabila, Nada; Raja, Patuan; Nurweni, Ari (Premise: Journal of English Education and Applied Linguistics, 2024)
This research analyzed speech acts that were uttered in the Validation short film. This study used pragmatics analysis to consider problems in English language learning, focusing on speech acts. This study aimed to classify the speech act in the Validation short film based on Searle's theory and the types of speech acts used in the Validation short film. This research used a descriptive qualitative method. The data used in this research included all of the utterances performed in the movie. The data analysis used a pragmatic approach based on Searle's theory. According to the theory, there are five classifications of speech act: representative, directive, commissive, expressive, and declarative. Searle discusses two types of speech acts: direct and indirect. It was found that the characters engaged in various classifications of speech acts, including representative, directive, commissive, and expressive. Notably, directive speech acts emerged as the most prevalent form employed by the characters. Additionally, direct speech acts were more frequently utilized than indirect ones. Future researchers are expected to conduct such research to analyze other aspects of pragmatics